2021
DOI: 10.3389/fendo.2021.735875
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Female Pelvic Ultrasonography in Differentiating Precocious Puberty From Premature Thelarche: A Systematic Review and Meta-analysis

Abstract: BackgroundThe gonadotropin-releasing hormone (GnRH) stimulation test is the benchmark for diagnosing precocious puberty (PP). However, it is invasive, time-consuming, costly, and may create an unpleasant experience for participants. Moreover, some overlaps may occur between PP and premature thelarche (PT) in the early stage of PP. Female pelvic ultrasonography may provide additional information to help differentiate PP from PT and subsequently initiate early treatment. In this study, we aimed to first directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Ovarian volume and the quantity of large follicles are generally inferior markers of puberty onset compared with uterine parameters 11 , 33 . On the other hand, a recent systematic review and meta-analysis of 13 studies found that girls with CPP had significantly greater uterine and ovarian measurements, and a uterine length greater than 3.20 cm was a reliable marker to differentiate CPP from IPT with a diagnostic odds ratio of 19.62 and an area under the curve of 0.820 34 . However, the PI was not evaluated in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian volume and the quantity of large follicles are generally inferior markers of puberty onset compared with uterine parameters 11 , 33 . On the other hand, a recent systematic review and meta-analysis of 13 studies found that girls with CPP had significantly greater uterine and ovarian measurements, and a uterine length greater than 3.20 cm was a reliable marker to differentiate CPP from IPT with a diagnostic odds ratio of 19.62 and an area under the curve of 0.820 34 . However, the PI was not evaluated in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…uterine and ovarian measurements could help to distinguish girls with CPP and isolated premature thelarche [ 14 , 32 , 33 ]. A recent meta-analysis noted that uterine length and volume are important markers for differentiating CPP from premature thelarche, e.g., a uterine length of 3.2 cm had a diagnostic AUC of 0.82, with a sensitivity and specificity of 81.8% and 82.0%, respectively [ 11 ]. FCR is regarded as a crucial indicator of puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of the brain can be used to determine the presence of brain lesions causing premature pubertal development. [ 10 , 11 ]. The possibility of replacing the GnRHa stimulation test with basal pubertal hormones, such as luteinizing hormone (LH) and routine imaging tests has been continuously reviewed [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian volume and the quantity of large follicles are generally inferior markers of puberty onset compared with uterine parameters [11,32]. On the other hand, a recent systematic review and meta-analysis of 13 studies found that girls with CPP had signi cantly greater uterine and ovarian measurements, and a uterine length greater than 3.20 cm was a reliable marker to differentiate CPP from IPT with a diagnostic odds ratio of 19.62 and an area under the curve of 0.820 [33]. However, the PI was not evaluated in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%